Sistem Pendukung Keputusan Untuk Menentukan Customer Segment Pasar Salah Satu UMKM Di Bandung ( Foodendez ) Dengan Metode Decision Tree - Dewayana, Baramukti; Wibowo, Ari Purnomo Wahyu (Jurnal Informatika UPGRIS, 2022)
Abstract Foodendez is a UMKM in Bandung which is well known for its products, namely Uthi Mies Krispi Patin Fish Skin which is a best seller product at Foodendez. This business has been running for about 5 years.In these 5 years Foodendez already has its own customer / market segment for the sale of this Foodendez product, however, this Foodendez has a problem predicting the customer / market segment for product sales from Foodendez, this is not suitable. expected expectations, because in analyzing / predicting customers / market segments still using a simple method or it can only be said to only use initial predictions by guessing roughly what estimates are known from the business plan or by other methods that make this Foodendez product get the wrong customer / segment that market It is expected that before hand or can be said to change and have an effect which makes Foodendez's turn over change insignificantly, and until recently Foodendez has not had a customer / market segment that is truly significant or as expected, for example is the sale of Krispi Patin Fish Skin that is predicted by the customer. the segment is more people 18 years old but it turns out that 18 years old people also like Krispi Patin Fish Skin products and offline and online sales where it is predicted that online sales will get a significant gain, which turns out to be more income in offline sales. So the authors provide a solution with the design / scheme of Decision Support Systems that will determine the customer segment and market segment which will later find out which market segment and customer segment are more significant and know which targets are suitable for products from Foodendez so that Foodendez UMKM can know what steps must be taken to set clear and significant targets by looking at the results of the percentage of enthusiasts and the turnover given by the Decision Tree method. The method of activities carried out is taken by collecting data with the interview method. The result of this activity is a Decision Support System design / scheme where the design / scheme is the result of determining a more detailed and significant customer segment / market segment and according to what the owner of Foodendez UMKM wants. Keywords: Decision Tree , Customer Segment , Market Segment , Foodendez , Uthi Mies